2017
DOI: 10.1063/1.4985710
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic hemispherical microphone array for three-dimensional acoustics

Abstract: This article describes the realization of a metamorphic stretchable microphone array, which can be inflated by air to morph from a planar to a hemispherical shape. The array undergoes morphological changes to adjust their receive characteristic. To realize this device, a metamorphic printed circuit board technology (m-PCB) is described. The resulting products are millimeter-thin stretchable silicone embedded and electrically interconnected electronic structures with mechanical properties, which resemble a sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In [18], the authors designed a localization algorithm for low-frequency sound based on a head-mounted microphone array. In [19], Biswas et al reported a metamorphic hemispherical microelectromechanical systems (MEMS) microphone array to estimate the location of a sound source in 3D space. In addition, Guo et al [20] introduced a 3 × 3 uniform rectangular array of 2D acoustic vector sensors with a miniaturized aperture to extract the directional acoustic modes.…”
Section: Introductionmentioning
confidence: 99%
“…In [18], the authors designed a localization algorithm for low-frequency sound based on a head-mounted microphone array. In [19], Biswas et al reported a metamorphic hemispherical microelectromechanical systems (MEMS) microphone array to estimate the location of a sound source in 3D space. In addition, Guo et al [20] introduced a 3 × 3 uniform rectangular array of 2D acoustic vector sensors with a miniaturized aperture to extract the directional acoustic modes.…”
Section: Introductionmentioning
confidence: 99%
“…A dramatic increase in research activities has been perceived for last decade to enable mechanically stretchable and deformable functional electronic devices 1–4 . Consequently, a large number of stretchable devices have been realized demonstrating a wide range of diverse applications that includes soft robotics 5,6 , actuators 7 , electronic eye cameras 8 , epidermal electronics 9 , wearable electronics 10,11 , metamorphic electronics 12,13 , edible electronics 14 , acoustoelectronics 15,16 , health monitoring devices 1719 , smart textiles 20 to give a few examples. Most of these demonstrators often use highly specialized technologies and unconventional materials that make these technologies more interesting for research, but less favorable for industrial production for mass people.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to fabricate soft, conformal, stretchable, and shape changing metamorphic electronic structures is of general interest due to the broad and pervasive range of immediate applications. These include wearable electronics [5], smart clothing [6], 3D acoustics [7], epidermal electronics [5], sensors [8], robotics [9], stretchable solid-state-lighting [10], stretchable LEDs [11], magnetoelectronics [12,13], and mechanically soft and conformable health monitoring devices [14].…”
Section: Introductionmentioning
confidence: 99%